2005
DOI: 10.1007/s00467-005-2082-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of renal osteodystrophy in children on chronic renal failure: European guidelines

Abstract: Childhood renal osteodystrophy (ROD) is the consequence of disturbances of the calcium-regulating hormones vitamin D and parathyroid hormone (PTH) as well as of the somatotroph hormone axis associated with local modulation of bone and growth cartilage function. The resulting growth retardation and the potentially rapid onset of ROD in children are different from ROD in adults. The biochemical changes of ROD as well as its prevention and treatment affect calcium and phosphorus homeostasis and are directly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(109 citation statements)
references
References 81 publications
2
93
0
14
Order By: Relevance
“…4,11,12,14,29 This study was not designed to determine the vascular effects of different PO 4 binders; sevelamer was used only as a second-line agent in our patients with persistently high iPTH levels and hypercalcemia. Goodman et al, 29 Litwin et al, 4 and Briese et al 33 showed a positive correlation between the cumulative PO 4 binder dosage and coronary calcification or cIMT, and in our study, IMT showed a weak correlation with PO 4 binder dosage approaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,11,12,14,29 This study was not designed to determine the vascular effects of different PO 4 binders; sevelamer was used only as a second-line agent in our patients with persistently high iPTH levels and hypercalcemia. Goodman et al, 29 Litwin et al, 4 and Briese et al 33 showed a positive correlation between the cumulative PO 4 binder dosage and coronary calcification or cIMT, and in our study, IMT showed a weak correlation with PO 4 binder dosage approaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…7 In recent years, attention has focused on the role of calcium (Ca), phosphate (PO 4 ), and parathyroid hormone (PTH) as potentially modifiable risk factors in the development and progression of vascular disease. 8 -10 Intact PTH (iPTH) levels of two to four times the upper limit of normal (ULN) are recommended for patients who are on dialysis 11,12 on the basis of bone histomorphometry studies in children 13 and adults. This is because as CKD progresses, continued stim-ulation of the parathyroid glands by high plasma PO 4 and low Ca levels leads to parathyroid gland hypertrophy and re-setting of the calcium-sensing receptor so that higher than normal levels of ionized Ca are required to alter PTH secretion.…”
mentioning
confidence: 99%
“…The eGFR was calculated with the new bedside Schwartz equation (19). Abnormalities in calcium, phosphorus, and PTH were assessed using European Pediatric Dialysis Working Group (EPDWG) guidelines on prevention and treatment of renal osteodystrophy in children on chronic renal failure (20) (Table 1). Although these guidelines are largely opinion based, they take into account the age dependency of mineral metabolism during childhood.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…Serum parathyroid hormone (PTH) levels are used as a biomarker of bone turnover; however, current treatment recommendations are opinion based and controversial in pediatric patients with predialysis CKD (2,3). Some data suggest that optimal growth is associated with serum PTH levels within the normal range (4), whereas other studies have demonstrated the greatest growth velocity at higher PTH levels (5).…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the actions of fibroblast growth factor 23 (FGF-23) has led to a new conceptual framework in understanding of the pathogenesis and treatment of CKD-MBD, with increasing levels in patients with CKD likely maintaining normophosphatemia at the expense of declining 1,25(OH) 2 vitamin D values (6). Previous studies in adult and pediatric patients have demonstrated that FGF-23 levels are elevated in early CKD and increase with CKD progression, suggesting that renal injury affects the skeleton in even very early stages of CKD (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%